Uniform Functionalization of High‐Quality Graphene with Platinum Nanoparticles for Electrocatalytic Water Reduction. Issue 3 (1st February 2015) - Mazzaro, Raffaello; Boni, Alessandro; Valenti, Giovanni; Marcaccio, Massimo; Paolucci, Francesco; Ortolani, Luca; Morandi, Vittorio; Ceroni, Paola; Bergamini, Giacomo
Abstract Graphene–metal composites have potential as novel catalysts due to their unique electrical properties. Here, we report the synthesis of a composite material comprised of monodispersed platinum nanoparticles on high‐quality graphene obtained by using two different exfoliation techniques. The material, prepared via an easy, low‐cost and reproducible procedure, was evaluated as an electrocatalyst for the hydrogen evolution reaction. The turnover frequency at zero overpotential (TOF0 in 0.1 m phosphate buffer, pH 6.8) was determined to be approximately 4600 h−1. This remarkably high value is likely due to the optimal dispersion of the platinum nanoparticles on the graphene substrate, which enables the material to be loaded with only very small amounts of the noble metal (i.e., Pt) despite the very highly active surface. This study provides a new outlook on the design of novel materials for the development of robust and scalable water‐splitting devices.